Frailty: A Review of the First Decade of Research. (October 2013) - Zaslavsky, Oleg; Cochrane, Barbara B.; Thompson, Hilaire J.; Woods, Nancy F.; Herting, Jerald R.; LaCroix, Andrea
Frailty is an emerging geriatric syndrome that refers to a state of increased vulnerability to adverse events including mortality, morbidity, disability, hospitalization, and nursing home admission. Despite its long conceptual and operational history in research and publications, frailty and mechanisms of frailty development are still poorly understood. In this review, we describe a number of conceptual models—reliability, allostatic load, and complexity—that have been put forward to explain the dynamic nature of frailty. We illustrate a consolidated pathophysiological model of frailty, taking into consideration the large and exponentially growing body of studies regarding predictors, indicators, and outcomes of frailty. The model addresses cellular (e.g., oxidative damage and telomere length) and systemic mechanisms (e.g., endocrinal, inflammatory, coagulatory, and metabolic deficiencies) of frailty, moderating or risk factors (e.g., ethnicity, lifestyle, and comorbidities), and outcomes (morbidity, disability, and cognitive decline). Finally, we identify the weaknesses of traditional epidemiological approaches for studying complex phenomena related to frailty and propose areas for future methodological and physiological inquiry.